Inclusive innovation bundling and scaling pathways for smallholders’ solar irrigation in Ethiopia - Dejen, Z. A.; Negera, M.; Tegegne, Desalegn; Mekuria, Wolde; Feysa, G. L.; Haileslassie, Amare (International Water Management Institute, 2025)
This report synthesizes key findings from field visits assessing existing solar irrigation practices, on-the-ground challenges, and opportunities for scaling solar irrigation systems. It analyzes systemic constraints limiting sustainable uptake beyond donor-supported pilots and proposes structured scaling strategies, with particular emphasis on technology bundling, institutional readiness, and financing mechanisms. While solar irrigation provides an alternative to diesel pumping and gravity diversion, the study emphasizes that water supply alone is insufficient to achieve sustainable irrigated agricultural development.